Fisheries in the Mediterranean - PAPACONSTANTINOU, C.; FARRUGIO, H. (Mediterranean Marine Science, 2000)
The aim of this paper is to give a description of the Mediterranean fisheries, and its level of exploitation and to address the main questions dealing with its management. The Mediterranean is a semi-enclosed marine area with generally narrow continental shelves. The primary production of the Mediterranean is among the lowest in the world (26-50g C m-2 y-1). The Mediterranean fisheries can be broken down into three main categories: small scale fisheries, trawling and seining fisheries, which operated on demersal, small pelagic and large pelagic resources. After a general description of the state of the resources in the different areas of the Mediterranean it is concluded that (a) the overall pictures from the western to the eastern Mediterranean are not considerably different, (b) the total landings in the Mediterranean have been increased the last decades, and (c) from the perspective of stock assessment, the very few available time series data show stable yield levels. In general fisheries management in the Mediterranean is at a rela- tively early stage of development, judging by the criteria of North Atlantic fisheries. Quota systems are generally not applied, mesh-size regulations usually are set at low levels relative to scientific advice, and effort limitation is not usually applied or, if it is, is not always based on a formal resource assessment. The conservation/management measures applied by the Mediterranean countries can be broadly separated into two major categories: those aiming to keep the fishing effort under control and those aiming to make the exploitation pattern more rational. The most acute problems in the management of the Mediterranean resources are the multispecificity of the catches and the lack of reliable official statistics.